Efficiency of zakat institutions in Malaysia: an application of data envelopment analysis - Abdul Wahab, Norazlina; Abdul Rahman, Abdul Rahim (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2012)
The aim of this paper is to measure the efficiency of zakat institutions in Malaysia during the period of 2003 to 2007. Using a Data Envelopment Analysis (DEA) technique, the results show that zakat institutions have exhibited mean technical efficiency of 80.6%. The results also suggest that pure technical inefficiency dominates the scale inefficiency effects in determining technical efficiency of zakat institutions in Malaysia. Further analysis of Spearman and Pearson correlation coefficients suggests that while higher Muslim population states tend to positively correlated to zakat collection, its correlation with efficiency score does not indicate a strong relationship, implying that it does not promise efficiency of zakat organization.